Pengaruh Scarcity Marketing, Perceived Value, Dan Customer Satisfaction Terhadap Purchase Intention Dalam Perspektif Ekonomi Islam (Studi Pada Konsumen Fashion E-commerce Shopee Di Bandar Lampung) - Jannah, Roihan Ruzikiani; Rifan, Dinda Fali Rifan; Rosilawati, Weny (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2024)
The rapid development of internet technology has driven the growth of e-commerce in Indonesia. Marketers increasingly utilize effective strategies like scarcity marketing to boost perceived value, leading to customer satisfaction and enhanced purchase intention. When consumers receive products that meet their expectations, satisfaction arises, ultimately influencing their buying decisions. This study uses a quantitative approach with data collected through online questionnaires involving 400 Generation Z respondents in Bandar Lampung. Sampling was conducted using quota sampling, and the data were analyzed using SmartPLS 4. The results reveal that scarcity marketing, perceived value, and customer satisfaction positively and significantly affect purchase intention. Scarcity techniques heighten product appeal, perceived value increases consumer confidence, and customer satisfaction strengthens purchase intention. From an Islamic perspective, Q.S. Ali-Imran verse 77 prohibits manipulation and false oaths in trade, emphasizing ethical practices in business